2022
DOI: 10.1242/dev.200527
|View full text |Cite
|
Sign up to set email alerts
|

Hbxip is essential for murine embryogenesis and regulates embryonic stem cell differentiation through activating mTORC1

Abstract: Hbxip, also named Lamtor5, has been well characterized as a transcriptional coactivator in various cancers. However, the role of Hbxip in normal development remains unexplored. Here, we demonstrated that homozygous knockout of Hbxip leads to embryonic lethality, with retarded growth around E7.5, and that depletion of Hbxip compromises the self-renewal of embryonic stem cells (ESCs), with reduced expression of pluripotency genes, reduced cell proliferation, and decreased colony forming capacity. In addition, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…For example, the self-renewal and differentiation of embryonic stem cells are regulated by mTORC1 signaling. In mice, knockout of HBXIP causes mTORC1 inactivation, which further affects the differentiation of embryonic stem cells and eventually leads to embryonic lethality ( 23 ).…”
Section: Normal Physiological Role Of Hbxipmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the self-renewal and differentiation of embryonic stem cells are regulated by mTORC1 signaling. In mice, knockout of HBXIP causes mTORC1 inactivation, which further affects the differentiation of embryonic stem cells and eventually leads to embryonic lethality ( 23 ).…”
Section: Normal Physiological Role Of Hbxipmentioning
confidence: 99%
“…The carcinogenic mechanism of HBXIP in most tumors has been established, but its role in normal cells has been less well studied. At present, the role of HBXIP in maintaining normal glucose tolerance phenotype and normal embryonic tissue development in mice has been preliminarily studied ( 22 , 23 ). Likewise, HBXIP is involved in DNA damage repair ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…CETSA and co‐immunoprecipitation revealed that nuciferine directly binds to the Ragulator subunit HBXIP) and impairs the interaction between the Ragulator complex and Rag GTPases, 126 which is crucial for the activation of mTORC1. 127 Due to its interaction with HBXIP and inhibition of mTORC1, nuciferine could activate TFEB‐mediated ALP by inhibiting TFEB phosphorylation at Ser211. Taken together, these results suggested that nuciferine may be a promising candidate for MAFLD treatment and that modulation of the mTORC1–TFEB–ALP axis represents a novel pharmacological therapy for MAFLD.…”
Section: The Effects and Functional Targets Of Natural Products In Th...mentioning
confidence: 99%
“…[ 20 ] Lamtor5 is originally recognized as an oncogenic protein with the ability to promote cellular proliferation and survival, [ 21 , 22 , 23 ] but recent data indicate that Lamor5 may have non‐carcinogenic roles such as the immunoregulatory function. [ 24 ] Global deletion of Lamtor5 caused embryonic lethality in mice, [ 25 ] implying a crucial and non‐redundant role for this molecule, of which we know little. Another critical but poorly understood question is whether the Ragulator component like Lamtor5 would interact with v‐ATPase and/or Rag GTPase to modulate mTORC1 activity.…”
Section: Introductionmentioning
confidence: 99%